2023
DOI: 10.3390/su16010324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Diffusion of Radon in Buildings and Mitigation Techniques

Alberto Pietro Damiano Baltrocchi,
Lucrezia Maggi,
Bruno Dal Lago
et al.

Abstract: Radon is a naturally occurring radioactive gas found in rocks, soil, and building materials. Precisely because of its gaseous nature, it tends to concentrate in indoor environments, resulting in a danger to human health. The effects of radon have been described, documented, and attested by the international scientific community and recognized as the second cause of lung cancer after cigarette smoking and in synergy with it. In December 2013, the Council of the European Union issued Council Directive 2013/59/Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…Overall, there was natural ventilation in 92.4% of the buildings where radon detectors were placed: 94.7% of the private detached houses and 88.7% of the multistory blocks of flats. The buildings with mechanical ventilation had significantly lower levels of radon than the ones with natural ventilation (31 (21,57) vs. 54 (30,94), p < 0.001; Table 1). The duration of the aeration of the buildings during summer slightly negatively correlated with the radon levels (r s = −0.105, p = 0.002), while the winter aeration pattern correlated less (r s = −0.066, p = 0.051).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Overall, there was natural ventilation in 92.4% of the buildings where radon detectors were placed: 94.7% of the private detached houses and 88.7% of the multistory blocks of flats. The buildings with mechanical ventilation had significantly lower levels of radon than the ones with natural ventilation (31 (21,57) vs. 54 (30,94), p < 0.001; Table 1). The duration of the aeration of the buildings during summer slightly negatively correlated with the radon levels (r s = −0.105, p = 0.002), while the winter aeration pattern correlated less (r s = −0.066, p = 0.051).…”
Section: Resultsmentioning
confidence: 94%
“…However, the study revealed a nuanced landscape where factors such as building age, type, presence of a cellar, and ventilation influence radon concentrations. Although many households fell within safe limits, a fraction exceeded recommended thresholds, which indicates that there are hidden radon exposure dangers [22,29,30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation